Enhancement of rutile phase formation in TiO2 films deposited on stainless steel substrates with a vacuum arc - Franco Arias, Lina Maria (2017)
The rutile phase of TiO2 has raised a wide interest for biomaterial applications. Since rutile is generally synthesized at high temperatures, a deposition process based on a cathodic arc discharge has been investigated in order to obtain rutile coatings at lower temperature on stainless steel substrates. In this work, TiO2 films were deposited on AISI 316 L stainless steel substrates heated at 300 and 400 °C with a negative bias of 120 V, employing Ti interlayers of different thicknesses. TiO2 films of approximately 500 and 900 nm were grown on Ti interlayers with thicknesses in the range 0–550 nm. The effect of Ti interlayers on the crystalline structure of TiO2 coatings was systematically studied with X-ray diffraction and Raman spectroscopy. The introduction of the Ti layer increased the rutile/anatase proportion either at 300 or 400 °C, turning rutile into the main phase in the TiO2 film. The largest amount of rutile for both temperatures was attained with a 55 nm Ti interlayer, the thinnest thickness studied.